2016
DOI: 10.3233/nua-150055
|View full text |Cite
|
Sign up to set email alerts
|

Wine consumption, cognitive function and dementias – A relationship?

Abstract: Abstract. Healthy cognitive function is essential for quality of life, wellbeing and independent living, and is negatively associated with dementias. A series of longitudinal and neuro-imaging studies in the elderly have shown that light to moderate wine consumption is neuro-protective although heavy or abusive alcohol consumption is neuro-toxic. A J-shaped relationship between alcohol consumption, cognitive dysfunction and risk of dementias is also observed for younger and middle aged consumers. There is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 151 publications
2
6
0
Order By: Relevance
“…While the harmful effects of heavy alcohol intake are well-established ( 2 ), several epidemiological studies have suggested that low to moderate consumption of red wine (~250 mL per day) can be beneficial in delaying the onset of cognitive impairments in aging and neurodegenerative diseases ( 3 – 8 ). In agreement with this, evidence from human randomized controlled trials shows that acute supplementations with specific wine compounds, such as anthocyanins or flavonoids, report improvements in recognition and working memory, attention, and psychomotor function ( 5 , 9 ). Moreover, in vivo studies in rodent models further support the idea that moderate red wine intake can impact cognitive function ( 10 12 ).…”
Section: Introductionsupporting
confidence: 53%
“…While the harmful effects of heavy alcohol intake are well-established ( 2 ), several epidemiological studies have suggested that low to moderate consumption of red wine (~250 mL per day) can be beneficial in delaying the onset of cognitive impairments in aging and neurodegenerative diseases ( 3 – 8 ). In agreement with this, evidence from human randomized controlled trials shows that acute supplementations with specific wine compounds, such as anthocyanins or flavonoids, report improvements in recognition and working memory, attention, and psychomotor function ( 5 , 9 ). Moreover, in vivo studies in rodent models further support the idea that moderate red wine intake can impact cognitive function ( 10 12 ).…”
Section: Introductionsupporting
confidence: 53%
“…Researchers are working to discover the relationship between the bioavailability of >200 phenolic compounds present in wine and their molecular and nutritional properties, environmental, social, or family factors that influence wine consumption, and the effects of alcohol on health. Although the benefits of polyphenols in fruit and vegetables are increasingly accepted, how wine, and in particular red wine with its abundant content of phenolic acids and polyphenols, provides further health benefits has not yet been fully clarified [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Moderate wine consumption, rather than alcohol consumption per se, has been related to a lower risk of AD (Nooyens et al, 2014). Wines contain polyphenols, a factor that distinguishes them from most other alcoholic beverages (Stockley, 2015). Wine polyphenols classified as flavonoids include anthocyanins, flavan-3-ols, flavonols, flavones, isoflavones, flavanones and non-flavonoids, including hydroxybenzoic acids, cinnamic acids and stilbenes (Cotea et al, 2012;Fanzone et al, 2012;Sen & Tokatli, 2014;Ren et al, 2017;Wojdyło et al, 2018).…”
Section: Introductionmentioning
confidence: 99%